A Prospective Study on Retinopathy of Prematurity in a Teritiary Care Center - Mahaboob Basha Kallur; K. Muralidhar (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Retinopathy of prematurity (ROP) is a vaso-proliferative retinopathy which occurs mostly in premature babies. The pathological change in ROP is peripheral retinal neovascularisation which may regress completely or leave sequelae from mild myopia to bilateral total blindness. International classification of ROP helped in uniform documentation and staging of ROP. In India, the incidence of ROP is between 38 and 51.9 p.c among low-birth-weight infants. Aim & Objectives: To estimate the incidence of ROP among premature and / or low birth weight babies who were born and admitted to neonatal intensive care unit and attending neonatal follow-up clinic.Subjects and Methods:A hospital based, prospective analytical cross-sectional study was conducted in Department of Pediatrics at Shadan Institute of Medical Sciences, Teaching hospital and research center, Hyderabad, Telangana for a period of 6 months from 1st October 2018 to 31st March 2019. Prior to the study initiation, ethical clearance was obtained and written consent was taken from the parents of the respective babies. The study subjects included premature babies (less than or equal to 35 weeks of gestation) or low birth weight babies (less than or equal to 1500 grams). A predesigned, pre-tested, semi-structured proforma was used to collected the data. The data was collected, entered in Microsoft excel-2013 and analyzed using SPSS version-22 (trial). Data was presented in percentages, proportions and figures.Result:The ROP incidence in the study group was reported among 17.1 p.c of the study subjects.Conclusion:Low birth weight and prematurity are important risk factors for ROP.